I centri minori italiani nel tardo medioevo (Centro di Studi sulla Civiltà del Tardo Medioevo San Miniato, 2018)
In the late Middle Ages, Italy was one of the most urbanized areas in Europe. Its coasts, the Apennines, the perialpine area and the plains were all home to a large number of smaller towns, lands, villages, castra, and 'quasi cites'. These settlements were all very diverse in terms of demographic consistency, social articulation and economic dynamism, but together they constituted a characteristic and constitutive element of the Italian historical identity: an 'original personality'. This volume, thanks to some framing essays and a mapping of individual cases involving most of the northern, central and southern regions, aims at investigating the active research on this topic over the last thirty to forty years.